2017
DOI: 10.4265/bio.22.153
|View full text |Cite
|
Sign up to set email alerts
|

Role of fatty acid salts as anti <i>Acanthamoeba</i> agents for disinfecting contact lens

Abstract: Acanthamoeba is found in seawater, fresh water, and soil and is an opportunistic pathogen that causes a potentially blinding corneal infection known as Acanthamoeba keratitis. The antiamoeba activity of 9 fatty acid salts potassium butyrate C4K , caproate C6K , caprylate C8K , caprate C10K , laurate C12K , myristate C14K , oleate C18:1K , linoleate C18:2K , and linolenate C18:3K was tested on Acanthamoeba castellanii ATCC 30010 trophozoites and cysts . Fatty acid salts 350 mM and pH 10.5 were prepared by mixin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 15 publications
4
16
0
Order By: Relevance
“…As noted in the scientific literature, 16,19,53,[80][81][82][83] the first report of AK was described by Nagington in 1974. 84 In the following years, AK was mainly related to ocular trauma.…”
Section: Incidencementioning
confidence: 97%
“…As noted in the scientific literature, 16,19,53,[80][81][82][83] the first report of AK was described by Nagington in 1974. 84 In the following years, AK was mainly related to ocular trauma.…”
Section: Incidencementioning
confidence: 97%
“…The results of this study suggest that the branched medium chain fatty acids have higher anti-amoeba effect on amoebae than their potassium salts. Previous anti-amoeba studies on A. castellanii showed a 4-log reduction in growth when treated with 175 mM potassium caprylate (C8K), potassium caprate (C10K), and potassium laurate (C12K) for 180 min [15]. In addition, cell membrane disruption was observed after mixing the amoeba suspension with C10K or C12K, and the MIC of C10K and C12K was 2.7 mM.…”
Section: A Effect Of Fatty Acids and Their Mics On Acanthamoeba Castmentioning
confidence: 93%
“…However, the disinfection effect of MPS is weaker than other contact lens disinfection methods, and hypersensitivity may occur, pointing to another disadvantage [12], [13]. Moreover, according to the 2009 National Consumer Center report in Japan, it was shown that anti-amoebic activity of commercially available MPS is very low [14], [15]. MPS contains polyhexanide hydrochloride as a main component [14], [16], [17], however, even after an incubation period of 8 hours, commercially available MPS decreased only 1/10 or less cells, in 4 of 8 strains [14], [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations